Analisis Publikasi Artikel Jurnal tentang Fenomena Fanatisme Agama di Indonesia dengan menggunakan Bibliometrik - Lintang Lituhayu (Gunung Djati Conference Series, 2023)
The purpose of this study is to examine the development of data from religious fanaticism starting from the number of publications, categories, authors and publishers. This study uses quantitative methods to identify the phenomenon of religious fanaticism in Indonesia with a bibliometric approach. This can provide progress and development in knowledge related to certain topics which in this case is religious fanaticism. The most active writer in researching religious fanaticism is Ahmad Zainal Abidin with the publication of five journals. The category that is often chosen in the research of religious fanaticism is philosophy and religious studies which has reached 912 journals. While the journal that publishes the most research on religious fanaticism is Islamica, a journal of Islamic studies with 36 journals. And a total of 1,833 journal publications on religious fanaticism from 2013-2022. The purpose of this paper is to find out the development of data regarding research on religious fanaticism which is expected to have an impact on religious scientific discussions and the media as well as become a reference for related policies.